Depression and quality of life among Macau residents in the 2022 COVID-19 pandemic wave from the perspective of network analysis - Si, Tong Leong; Chen, Pan; Zhang, Ling; Sha, Sha; Lam, Mei Ieng; Lok, Ka-In; Chow, Ines Hang Iao; Li, Jia-Xin; Wang, Yue-Ying; Su, Zhaohui; Cheung, Teris; Ungvari, Gabor S.; et al. (Frontiers in Psychology, 2023)
Background: In the summer of 2022, Macau experienced a surge of COVID-19 infections (the 618 COVID-19 wave), which had serious effects on mental health and quality of life (QoL). However, there is scant research on mental health problems and QoL among Macau residents during the 618 COVID-19 wave. This study examined the network structure of depressive symptoms (hereafter depression), and the interconnection between different depressive symptoms and QoL among Macau residents during this period. Method: A cross-sectional study was conducted between 26th July and 9th September 2022. Depressive symptoms were measured with the 9-item Patient Health Questionnaire (PHQ-9), while the global QoL was measured with the two items of the World Health Organization Quality of Life-brief version (WHOQOL-BREF). Correlates of depression were explored using univariate and multivariate analyses. The association between depression and QoL was investigated using analysis of covariance (ANCOVA). Network analysis was used to evaluate the structure of depression. The centrality index "Expected Influence" (EI) was used to identify the most central symptoms and the flow function was used to identify depressive symptoms that had a direct bearing on QoL. Results: A total 1,008 participants were included in this study. The overall prevalence of depression was 62.5% (n=630; 95% CI=60.00-65.00%). Having depression was significantly associated with younger age (OR=0.970; P<0.001), anxiety (OR=1.515; P<0.001), fatigue (OR=1.338; P<0.001) and economic loss (OR=1.933; P=0.026). Participants with depression had lower QoL (F (1,008) =5.538, P=0.019). The most central symptoms included PHQ2 ("Sad Mood") (EI: 1.044), PHQ4 ("Fatigue") (EI: 1.016), and PHQ6 ("Guilt") (EI:0.975) in the depression network model, while PHQ4 ("Fatigue"), PHQ9 ("Suicide"), and PHQ6 ("Guilt") had strong negative associations with QoL. Conclusion: Depression was common among Macao residents during the 618 COVID-19 wave. Given the negative impact of depression on QoL, interventions targeting central symptoms identified in the network model (e.g., cognitive behavioural therapy) should be developed and implemented for Macau residents with depression.